2019
DOI: 10.14742/ajet.4577
|View full text |Cite
|
Sign up to set email alerts
|

The decorative images’ seductive effect in e-learning depends on attentional inhibition

Abstract: Two studies sought to replicate and extend the seductive effect of decorative pictures in expository text comprehension to an e-learning environment. In the first study, undergraduate students read and answered questions about two texts, with and without decorative, irrelevant images, in an e-learning course. The presence of decorative images had a small detrimental effect on comprehension. In the second study, participants read more difficult texts (low prior knowledge texts in multiple screens) and completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Seductive details are thought to impose extraneous load on limited working memory capacity or distract attention. In this sense, inhibition control could be relevant regarding the seductive nature of the effect (González et al, 2019). Indeed, overcoming the seductive details effect requires a high level of inhibitory control, which according to Diamond (2013), can function on an attentional (preventing attention to focus on irrelevant information) and/or cognitive level (deleting irrelevant information that causes extraneous load on working memory).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seductive details are thought to impose extraneous load on limited working memory capacity or distract attention. In this sense, inhibition control could be relevant regarding the seductive nature of the effect (González et al, 2019). Indeed, overcoming the seductive details effect requires a high level of inhibitory control, which according to Diamond (2013), can function on an attentional (preventing attention to focus on irrelevant information) and/or cognitive level (deleting irrelevant information that causes extraneous load on working memory).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In conclusion, evidence supported the hypothesis of a detrimental effect of irrelevant, decorative images on comprehension in e-learning, particularly for students with low attentional inhibition. So based on this research, unclear images displayed during learning will become an obstacle to understanding the material and are considered a form of distraction [19].…”
Section: Introductionmentioning
confidence: 97%
“…This effect can be explained by the limitation of learners' cognitive resources, especially the capacity of their working memory and attention channels (Sweller, Ayres, & Kalyuga, 2011); furthermore, irrelevant information may interrupt the development of learning‐relevant schemata (for a meta‐review, see Rey, 2012). Many factors can influence the effect, for instance, of arousal (Schneider, Wirzberger, & Rey, 2019) or low attentional inhibition (González, Saux, & Burin, 2019). Even though some researchers showed that decorative pictures impeded learning, these pictures improve learning when learning‐relevant emotions are simultaneously activated or the pictures are integrated into a learning context (Schneider et al, 2016; Schneider, Dyrna, Meier, Beege, & Rey, 2018; Schneider, Nebel, Beege, & Rey, 2018).…”
Section: Introductionmentioning
confidence: 99%